Prevalence of multi-drug resistant tuberculosis and factors associated with treatment outcome in three districts of Himachal Pradesh, India - Verma, Pushpinder; Singh, Balbir; Shridhar, Pramod K.; Singh, Gurmeet; Singh, Sukhjinder Pal; Rajdev, Parth (International Journal Of Community Medicine And Public Health, 2021)
Background: Tuberculosis (TB) is a leading cause of morbidity and mortality in the world and especially in India. MDR TB has emerged as a major challenge in TB control in India. The prevalence of MDR TB is on the rise in India. We did this study to see the prevalence of MDR TB in 3 districts of Himachal Pradesh and to study the factors affecting treatment outcomes. Methods: The period of the study was from January 2019 to December 2019. We collected data of MDR TB patients from district TB offices of Solan, Bilaspur and Hamirpur. Information from patients was collected through questionnaires while interviews were conducted with district project officer and other health officials and documents, brochures, etc. were collected from Solan, Hamirpur and Bilaspur. Results: Overall prevalence rate of MDR TB in our study was 3.14%. Among new TB cases, the prevalence rate of MDR TB was 2.42% (81/3345), and among old treated cases was 9% (37/411). 31% MDR TB patients were old treated while 69% patients had no previous treatment history. The default rate was low in our study (0.84%) while 8 (6.4%) patients had treatment interruption but for less than 15 days. Conclusions: The prevalence in our study is comparable to the national drug resistance survey. Early detection, timely treatment and contact tracing is vital in decreasing the MDR TB cases. Better supervision, constant monitoring, proper counselling and timely identification and management of adverse effects of the drugs will improve the treatment outcome among MDR TB patients.